2015
DOI: 10.25300/misq/2015/39.3.03
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Minority and Silent Majority: How Do Online Ratings Reflect Population Perceptions of Quality?

Abstract: Consumer-generated ratings typically share an objective of illuminating the quality of a product or service for other buyers. While ratings have become ubiquitous and influential on the Internet, surprisingly little empirical research has investigated how these online assessments reflect the opinion of the population at large, especially in the domain of professional services where quality is often opaque to consumers. Building on the word-ofmouth literature, we examine the relationship between online ratings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(123 citation statements)
references
References 69 publications
1
120
0
2
Order By: Relevance
“…A ideia de "minoria barulhenta" (vocal minority) tem permeado discussões sobre opinião pú-blica, com especial ênfase recente (Gao, Greenwood, Agarwal, & McCullough, 2015). A questão se refere a como determinados grupos, embora minoritários, possam ser também mais atuantes, criando uma falsa percepção, perante a opinião pública, de suas grandezas e influência.…”
Section: Algumas Considerações E Potenciaisunclassified
“…A ideia de "minoria barulhenta" (vocal minority) tem permeado discussões sobre opinião pú-blica, com especial ênfase recente (Gao, Greenwood, Agarwal, & McCullough, 2015). A questão se refere a como determinados grupos, embora minoritários, possam ser também mais atuantes, criando uma falsa percepção, perante a opinião pública, de suas grandezas e influência.…”
Section: Algumas Considerações E Potenciaisunclassified
“…Examples of strategies for manipulating ratings include colluding with others to provide false ratings, paying others to provide false ratings, and using multiple accounts to provide false ratings of one's self. Despite the existence of these strategies for manipulating ratings posted using online reputation systems, Gao, Greenwood, Argarwal, and McCullough (2015) found a positive correlation between online reviews of physician quality and offline surveys completed by the population of patients. Although the results of their study suggest that physician reviews collected in online reputation systems may have fewer information quality problems than some suspect, Gao et al (2015) found a bias in these reviews with an overrepresentation of more favorable online ratings of physicians.…”
Section: Background On Online Reputation Systemsmentioning
confidence: 99%
“…The most common eWOM is online rating. In the study of the relationship between online scoring and mass perception in the medical field, it was found that the lower perceived quality evaluators received less online scores; online scoring was positively correlated with quality (Gao, Greenwood and McCullough, 2015). Therefore, this paper measures the customer performance with the mean value of the customer's scores of taste, environment, and service ratings.…”
Section: Dependent Variablementioning
confidence: 99%